School organisation and administration - Sidhu, Kulbir Singh (New Delhi : Sterling publisers private, 2002)
Contents: school organisation and administration challenges of school organisation and administration democracy and administration the school plant the headmaster the teacher school time table school discipline cocurricular activities punishments and rewards school records supervision and inspection institutional planning library and reading room physical education health education evaluation school and community controlling authorities educational ladder school complex.
Keywords: Labor discipline -- United States; School personnel management -- United States; Documentation -- United States; School employees -- Dismissal of -- United States